Bis(O,O′-diphenethyl dithiophosphato-κ(2) S,S′)bis(4-methylpyridine-κN)nickel(II) - Feng, Jian-Shen (International Union of Crystallography, 2008)
The title complex, [Ni(C(16)H(18)O(2)PS(2))(2)(C(6)H(7)N)(2)], exhibits a roughly octahedral coordination geometry. The Ni(II) atom lies on an inversion centre and is coordinated by four S atoms of O,O′-diphenethyl dithiophosphate molecules and two N atoms of 4-methylpyridine molecules. Important geometric data include Ni—N = 2.100 (3) Å, and Ni—S = 2.5101 (10) and 2.4772 (11) Å.